Social Thinking Metacognitive Strategies to Support Self-Determined Social Goals in Autistic Youth - Crooke, Pamela J.; Winner, Michelle Garcia (Seminars in Speech and Language, 2022)
On any given day, the social mind is taxed with attending to and making sense of a myriad of social events. The social mind is at work when trying to imagine the experiences of others and their inner mental worlds, and is equally active when people seek to approach, connect with, and sometimes avoid one another. Ultimately, the social mind is responsible for thinking about (social) thinking, or social metacognition. Social metacognitive teaching strategies can be helpful for supporting social learners as they observe social landscapes, interpret what is observed to problem solve, or decide whether and how to produce social responses. This article describes how social metacognitive strategies from the Social Thinking Methodology have been used to support the self-determined social goals of two autistic students. Visual frameworks and their underlying theories are provided as evidence-aligned tools for supporting clinical journeys.
Keywords: social metacognition; social competency; social thinking; social cognition; self-determination